RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN JASA PELAMINAN (Studi Kasus : Gadih Nan Tongga Wedding) - Haswir, Siti Almira; Budayawan, Khairi (INCARE, International Journal of Educational Resources, 2021)
Wedding rental services are one of the services needed at this time. Especially for the bride and groom and their families who want to hold a wedding reception that is in accordance with a predetermined schedule. The problem faced in the aisle rental system at Gadih Nan Tongga Wedding is that customers must come directly to locations far from the city center. The ordering process in addition to coming directly to the location also uses an instant messenger application, namely WhatsApp. In addition, the administration department in recording customer orders still uses a very simple way where the administration section writes the order in a book only. . Then the file can be lost or scattered, even burnt and wet and eaten by termites because the files that are made still use paper. To produce a web-based service ordering information system, the author uses the CodeIgniter framework from PHP which is based on the MVC (Model View Controller) model.